From Underground to the Spotlight. Finnish Minimal Techno in the 1990s. - Grönholm Pertti (Routledge, 2022)
In Chapter 10, Pertti Grönholm gives an overview of the process in which Finnish minimal techno music became known internationally from the 1990s onward. A small group of underground techno artists, who were fascinated by 1980s Detroit techno, industrial, and experimental electronic music, gained attention for their raw and authentic, indeed “minimal,” sound. Foreign journalists, baffled by the introverted silence of the experimental Finns like Kimmo Rapatti, Mika Vainio, and Ilpo Väisänen, started to explain their stylistic choices by describing the harsh living conditions in Finland, the cold and dark winters where these alcohol-consuming, sauna-loving creatures conjured their authentic music in silence. Sounds familiar, doesn’t it? Needless to say, these artists were more than happy to play along with these cultural stereotypes, giving journalists the heart of darkness as well as they could. Also, the visual quality of Sähkö Recordings – the most influential of Finnish electronic music underground labels – releases followed the same minimal aesthetic as the aural production. In his chapter, Grönholm also introduces earlier features of Finnish electronic music since the 1970s. The narrative flows from experimental music to progressive rock, disco, gothic rock, industrial, humorous rap, and rave culture. Finally, the story culminates with the massive international breakthrough of Finnish electronic music at the start of the millennium when more commercial outfits, mostly produced by Jaakko Salovaara like Bomfunk MC’s and Darude, topped international charts. If the slick sounds of Finnish house, trance, hip hop, and even the cool hipster jazz sounds of Jimi Tenor provided a certain kind of celebratory Finnish face for global fans of electronic music, it is the “brutalist minimalist” under-ground experimentation of Pan Sonic that might have had the most lasting impact.
Made in Finland. Studies in Popular Music.